Age of Entry Into Early Childhood Education and Care as a Predictor of Aggression: Faint and Fading Associations for Young Norwegian Children. (October 2015) - Dearing, Eric; Zachrisson, Henrik Daae; Nærde, Ane
Socioemotional risks associated with nonparental care have been debated for decades, and research findings continue to be mixed. Yet few studies have been able to test the causal hypothesis that earlier, more extensive, and longer durations of nonmaternal care lead to more problems. To examine the consequences of age of entry into nonparental care for childhood aggression, we used prospective longitudinal data from Norway, where month of birth partly determines age of entry into Early Childhood Education and Care (ECEC) centers. In this sample of 939 children followed from ages 6 months through 4 years, ECEC teachers reported the children's aggression when they were 2, 3, and 4 years old. We found some evidence that age of entry into ECEC predicted aggression at age 2, albeit modestly and not robustly. Between the ages of 2 and 4 years, the effect of age of entry on aggression faded to negligible levels. The implications for psychological science and policy are discussed.